Seasonal changes in group size and foraging activity in an urban population of Magpies ("Pica pica") - Jerzak, Leszek; Ciebiera, Olaf; Boehner, Joerg (Zielona Góra: University of Zielona Góra, Faculty of Biological Sciences)
We studied seasonal variation in group size and feeding activity in an urban population of Magpies in Zielona Gora, Western Poland. Each month from 1984 to 1987 we counted the species along a 10 km transect across the city and noted the number of single birds, pairs and flocks as well as flock size. In 1999 and 2000 we regularly observed Magpies foraging on the lawns of a park of Zielona Gora and recorded the number of pecks, as a measure for feeding activity.
Keywords: Magpie; urban population; group size; foraging activity